A machine learning approach to detect DeepFake videos - Hassan, Md. Mahedi; Nawrin, Na sha (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.